Consumer Preferences for The Quality of Product Attributes of Palm Sugar in Mataram City - Ilhamudin, M.; Masrun, Masrun (ProBisnis : Jurnal Manajemen, 2024)
This study aims to find out consumer preferences for the attributes of palm sugar products produced by West Lombok MSMEs sold in the traditional markets of Mataram city. The study population is all palm sugar consumers who come to make purchases in several predetermined traditional markets. This study uses a survey sample method, and uses a purposive sampling technique. Because the number of members of the research population is not known for sure, the number of research samples is determined to be 100 respondents. To answer the problems raised, the analysis tool used is the Ideal-Point Model, which is the evaluation of consumers on what they feel and what they want. This model measures the difference between what is perceived and what consumers want. The results of the study show that the attributes of palm sugar products are good. This is shown by the quality value being in the middle interval class, which means that the quality of the product is quite in accordance with consumer desires.